Mitochondrial Disorder Aggravated by Metoprolol - Cheryl Samuels; Mary Kay Koenig; Mariana Hernandez; Aravind Yadav; Ricardo A. Mosquera (Hindawi Limited, 2016)
Beta-adrenergic blocking agents or beta-blockers are a class of medications used to treat cardiac arrhythmias and systemic hypertension. In therapeutic dosages, they have known adverse outcomes that can include muscular fatigue and cramping, dizziness, and dyspnea. In patients with mitochondrial disease, these effects can be amplified. Previous case reports have been published in the adult population; however, their impact in pediatric patients has not been reported. We describe a pediatric patient with a mitochondrial disorder who developed respiratory distress after metoprolol was prescribed for hypertension. As the patient improved with discontinuation of medication and no alternative etiology was found for symptoms, we surmise that administration of metoprolol aggravated his mitochondrial dysfunction, thus worsening underlying chest wall weakness.